Economic evolution in Euro-adopting states vs. future adopters: A comparative analysis - Nicoleta Georgeta Panait; Madalina Antoaneta Radoi (Economies, 2025)
This paper analyzes the macroeconomic evolution of the European Union member states that have adopted the Euro, compared to those that continue to use national currencies, with a specific focus on the Central and Eastern European countries during the period 2018-2024. Using a quantitative and exploratory approach and data provided by Eurostat, the European Central Bank, and the International Monetary Fund, we examined a series of key indicators: interest rates, inflation, GDP per capita, public debt, and foreign direct investment. The results highlight several macroeconomic advantages for Eurozone countries, including lower interest rate volatility and a quicker recovery from inflation, largely due to access to monetary tools such as PEPP and TPI. Non-Euro countries have experienced more severe inflationary episodes and higher financing costs, which have negatively impacted FDI inflows. Although some of these countries, such as Romania and Poland, have recorded solid GDP growth, they remain exposed to structural vulnerabilities and political and economic uncertainties. Correlation analyses confirm significant negative relationships between interest rates, inflation, and FDI levels.
Keywords: 330; monetary policy; convergence; FDI; GDP; inflation; interest rates; non-Euro countries